ASPARTATE AND ALANINE AMINOTRANSFERASE ACTIVITIES IN FISH TISSUE SUBCELLULAR FRACTIONATION ON EXPOSURE TO AMBIENT UREA - Rajyasree, M; Neeraja, P (Indian Journal of Fisheries, 2011)
Quantitative estimation of mitochondrial and cytosolic aspartate aminotransferase (AA T) and alanine aminotransferase(AlA T) specific activity levels in liver, muscle, brain and gill tissues of Labeo Tohita exposedto 50 ppm commercial urea for 15, 30 and 60 days has been done. Active transamination was observed incytosolic fractions of all tissues. AAT showed maximum in muscle mitochondrial fraction whereas AIATshowed maximum activity both in muscle mitochondrial and cytosolic fractions.